Peran E-commerce Sebagai Media Komunikasi Bisnis Dalam Peningkatan Penjualan UMKM Salaut Di Universitas Teknologi Digital - Apprilisda Ranica Putri; Devi Maria Saadah; Iis Nurkamillah; Silven Yonathan; Sucya Sri Yuliana; Ricky Firmansyah (Institut Nalanda, 2023)
Technological growth has changed not only the way people talk, but also the way trading is done. The growth of e-commerce that continues to be useful has become an available place for entrepreneurs to buy and sell goods online. This opportunity should not be missed by Micro, Small and Medium Enterprises (SMEs), such as Salaut MSMEs, which are used by business owners to promote their products in e-commerce. The obstacles experienced by MSMEs so far have been a marketing problem, especially for MSMEs in the regions. Social media is still an individual activity, this is still seen among MSMEs players, social media is not really considered as part of strategic activities on behalf of business. MSMEs are part of the focus, because competence in mastering the IT field is still very diverse, the focus of MSMEs starts from a close context, urging MSME participation through the use of affordable media according to the consuming capacity of UKM. The arrival of e-commerce is an opportunity for MSMEs, because using a marketplace can allow MSMEs to have a wider market and cheaper promotions. In terms of sales promotion, the advantage of SMEs selling through online platforms is that they can attract a wider range of customers. Everyone connected to the Internet can view promotions without geographic boundaries. The design approach that the author uses in building this paper is the use of a qualitative method. Having this daily supports the transaction process and product promotion of MSMEs Salaut Digital Technology University, making it more efficient and effective.